Preparation method of oxide dispersion strengthened austenitic stainless steel and application of nuclear fuel cladding material
By adding Zr to oxide dispersion strengthened austenitic stainless steel, a refined Zr-YO dispersed phase and Al2O3 protective oxide film are formed, which solves the corrosion resistance and radiation swelling problems of oxide dispersion strengthened steel in supercritical environment and realizes the efficient application of the material in nuclear reactor cladding material.
Patent Information
- Application Number
- CN202510652821.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-10-03
AI Technical Summary
Existing oxide dispersion strengthened steels have poor corrosion resistance in supercritical water/supercritical carbon dioxide cooled nuclear reactors, and aluminum-containing austenitic stainless steels are prone to radiation swelling and failure, making it difficult to meet the service requirements of cladding materials.
By adding Zr to form a refined Zr-YO dispersed phase and an Al2O3 protective oxide film, combined with a method for preparing austenitic stainless steel with oxide dispersion strengthening in a specific element ratio, including vacuum melting, ball milling, hot isostatic pressing and other steps, a corrosion-resistant and radiation-resistant material is prepared.
A continuous Al2O3 oxide film is generated in supercritical water and supercritical carbon dioxide, and the dispersed phase captures radiation defects, thereby improving the material's corrosion resistance and resistance to radiation swelling.
Smart Images

Figure CN120738564A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of alloys, and in particular relates to a preparation method of oxide dispersion strengthened austenitic stainless steel and application of nuclear fuel cladding materials. Background Art
[0002] Supercritical water-cooled nuclear reactors and supercritical carbon dioxide-cooled nuclear reactors are important candidates for next-generation nuclear reactors. They can increase nuclear reactor efficiency to ~45%, offering significant economic advantages. Cladding, the material that holds the nuclear fuel in a nuclear reactor, is the reactor's primary safety barrier and one of its most critical materials.
[0003] Supercritical water / supercritical carbon dioxide (SCW / SCCO2)-cooled nuclear reactors share a common characteristic: high operating temperatures (reactor outlet temperature ≥ 500°C). High-temperature SCW and SCCO2 are both highly corrosive, placing severe demands on the corrosion resistance of cladding materials. Furthermore, SCW / SCCO2-cooled cladding materials are also subject to the most severe neutron irradiation in nuclear reactors. Therefore, developing new, corrosion- and radiation-resistant cladding materials is a key prerequisite for the successful design and construction of SCW / SCCO2-cooled nuclear reactors.
[0004] Traditional zirconium alloy cladding materials are completely unable to meet the requirements of the strong radiation and high corrosion environment faced by the cladding materials of supercritical water / supercritical carbon dioxide cooled nuclear reactors. In recent years, oxide dispersion strengthened (ODS) steel has become an important candidate for the next generation of nuclear reactor cladding materials due to its excellent radiation resistance. However, the matrix of current oxide dispersion strengthened steel is mostly iron horse steel (Cr mass fraction is 9%-12%), which has poor corrosion resistance in supercritical water / supercritical carbon dioxide and is difficult to meet its requirements. Austenitic stainless steel has better corrosion resistance, but traditional commercial austenitic stainless steel, such as 316LN and 304L stainless steel, has a fast corrosion rate in supercritical water / supercritical carbon dioxide and is difficult to meet the strong corrosion requirements of supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials in service. In recent years, new aluminum-containing austenitic stainless steels have become an important development direction for cladding materials for supercritical water / supercritical carbon dioxide cooled nuclear reactors because they can form an Al2O3 protective oxide film in supercritical water and supercritical carbon dioxide. However, austenitic stainless steels are prone to radiation swelling and failure, which has become a key obstacle to their application. Therefore, combining the radiation resistance of oxide dispersion strengthened steels with the corrosion resistance of aluminum-containing austenitic stainless steels, the development of oxide dispersion strengthened aluminum-containing austenitic stainless steels has become an important development direction for the design and manufacture of cladding materials for supercritical water / supercritical carbon dioxide cooled nuclear reactors.
[0005] However, Al reacts with Y2O3 at high temperatures to form a coarse Al-YO phase, significantly reducing the number density of the oxides and, consequently, the radiation resistance and mechanical properties of the material. Studies have shown that the oxide formation energy of Zr is lower than that of metallic Al, and that the diffusion coefficient of Zr metal in the Fe matrix is smaller than that of Al. Therefore, research on slowing the nucleation and aggregation of metal oxides by adding Zr, thereby refining the oxide particles and forming Zr-YO instead of coarse Al-YO, has become an important technical approach. Therefore, through reasonable technological innovation, supporting the design and preparation of new aluminum-containing austenitic stainless steels with oxide dispersion strengthening, it is possible to develop corrosion-resistant and radiation-resistant materials that meet the requirements of supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials. Summary of the Invention
[0006] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide an oxide dispersion strengthened austenitic stainless steel.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: an oxide dispersion strengthened austenitic stainless steel, characterized by containing the elements Cr, Ni, Al, Mo, Nb, Zr, Y2O3, C and Fe;
[0010] Calculated based on the mass fraction of the raw materials, the mass fraction of Cr is 20.0-22.0wt.%, the mass fraction of Ni is 28.0-30.0wt.%, the mass fraction of Al is 2.0-3.0wt.%, the mass fraction of Mo is 1.0-2.0wt.%, the mass fraction of Nb is 0.6-1.0wt.%, the mass fraction of Zr is 0.1-0.4wt.%, the mass fraction of Y2O3 is 0.05-0.15wt.%, the mass fraction of C is 0.06-0.1wt.%, and the balance is Fe.
[0011] As a preferred embodiment of the oxide dispersion-strengthened austenitic stainless steel of the present invention, the oxide dispersion-strengthened austenitic stainless steel, calculated by mass fraction, comprises: 21.0 wt.% Cr; 29.0 wt.% Ni; 2.5 wt.% Al; 1.5 wt.% Mo; 0.6 wt.% Nb; 0.2 wt.% Zr; 0.08 wt.% Y2O3; 0.08 wt.% C; and the remainder is Fe.
[0012] As a preferred embodiment of the oxide dispersion strengthened austenitic stainless steel of the present invention, the above-mentioned stainless steel further has the following characteristics:
[0013] (i) Corrosion in 550℃ / 25MPa supercritical water for 2000h resulted in a weight increase of 14.26-14.72mg·dm2;
[0014] (ii) Corrosion in supercritical carbon dioxide at 550°C / 25 MPa for 2000 h increases weight by 5.45-5.53 mg·dm2;
[0015] (iii) the swelling ratio after 50 dpa of Fe ion irradiation at 550 °C was 0.31–0.34%;
[0016] (iiii) The tensile elongation at 550°C is 35.2-36.4%.
[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing oxide dispersion strengthened austenitic stainless steel, which is characterized by comprising:
[0018] Fe, Cr, Ni, Nb, Mo and C are mixed and then vacuumed and sent for electric melting. After the steel is liquefied and cleared, Al and Zr are added and refined under vacuum conditions, followed by pouring, forging, heat treatment and gas atomization powder spraying to obtain master alloy powder.
[0019] Zr powder and Y2O3 powder were ball-milled in a high-purity argon atmosphere to obtain Zr-YO powder;
[0020] The master alloy powder and the Zr-YO powder are ball-milled in a high-purity argon atmosphere to obtain a mixed powder;
[0021] The mixed powder is hot isostatically pressed and solidified, and then forged and heat treated to obtain the compound dispersion strengthened austenitic stainless steel.
[0022] As a preferred embodiment of the preparation method of the present invention, the refining temperature is 1470-1530° C. and the refining time is 8-12 minutes.
[0023] As a preferred embodiment of the preparation method of the present invention, the Zr powder and Y2O3 powder are ball-milled in a high-purity argon atmosphere to obtain Zr-YO powder, wherein the mass ratio of Zr to Y elements is not less than 1.03, and the total mass of Zr powder and Y2O3 powder is not less than 100 g; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-material ratio is 5 to 10:1, the ball milling time is 25 to 50 hours, and the rotation speed is 200 to 400 r / min.
[0024] As a preferred embodiment of the preparation method of the present invention, the master alloy powder and Zr-YO powder are ball-milled and mixed in a high-purity argon atmosphere to obtain a mixed powder, wherein the mass of the Zr-YO powder is controlled so that the total content of Y2O3 does not exceed 0.15%; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-material ratio is 6 to 12:1; the ball milling time is 50 to 150 hours, and the rotation speed is 150 to 300 r / min.
[0025] As a preferred embodiment of the preparation method of the present invention, the mixed powder is hot isostatically pressed and solidified and then forged, wherein the forging conditions are an initial forging temperature of 1100-1200°C, a final forging temperature of not less than 950°C, and a total forging ratio of not less than 4:1.
[0026] As a preferred embodiment of the preparation method of the present invention, the heat treatment includes solution treatment and aging, wherein the solution treatment temperature is 1100-1200°C and the holding time is 1-2 hours; the aging temperature is 550-650°C and the holding time is 100-200 hours.
[0027] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of oxide dispersion strengthened austenitic stainless steel in supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials.
[0028] Beneficial effects of the present invention:
[0029] This invention provides a method for preparing oxide-dispersion-strengthened austenitic stainless steel and its application as a nuclear fuel cladding material. This material forms a continuous protective Al2O3 oxide film in supercritical water and supercritical carbon dioxide, exhibiting excellent corrosion resistance. Furthermore, the interface formed between the dispersed micro- and nano-precipitates (such as Zr-YO and Ni3Al) and the matrix absorbs radiation defects, ensuring the material's excellent resistance to radiation swelling. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort. Among them:
[0031] Figure 1 This is a morphology diagram of dispersed oxides in the oxide dispersion strengthened new austenitic stainless steel material obtained in Example 1 of the present invention.
[0032] Figure 2 This is the morphology of the oxide film of Example 1 of the present invention after being corroded in 550°C supercritical water for 1000 hours.
[0033] Figure 3 This is the morphology of the oxide film of Example 1 of the present invention after being corroded in supercritical carbon dioxide at 550°C for 1000 hours.
[0034] Figure 4 This is a photo of the irradiated voids obtained after irradiation with 5MeV iron ions at 550°C in Example 1 of the present invention.
[0035] Figure 5 Schematic diagram of the dynamic circulating supercritical water corrosion system used in the test of the present invention.
[0036] Figure 6 Schematic diagram of the dynamic circulating supercritical carbon dioxide corrosion system used in the test of the present invention. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.
[0040] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available. Details are shown in Table 1.
[0041] Table 1
[0042] name Commercial channels High-purity nickel powder China Metallurgical Research Institute provides direct supply to universities and enterprises for scientific research High-purity iron powder China Metallurgical Research Institute provides direct supply to universities and enterprises for scientific research High purity molybdenum powder China Metallurgical Research Institute provides direct supply to universities and enterprises High purity chromium powder China Metallurgical Research Institute provides direct supply to universities and enterprises for scientific research High purity niobium powder China Metallurgical Research Institute provides direct supply to universities and enterprises High-purity graphite powder China Metallurgical Research Institute provides direct supply to universities and enterprises for scientific research High-purity aluminum particles China Metallurgical Research Institute provides direct supply to universities and enterprises High-purity zirconium particles Zhongke Yannuo High-purity yttrium oxide powder Zhongke Yannuo
[0043] Example 1
[0044] This embodiment provides a method for preparing oxide dispersion strengthened austenitic stainless steel for use as a cladding material for supercritical water / supercritical carbon dioxide cooled nuclear reactors:
[0045] The raw material composition is as follows in terms of mass percentage: Cr: 21.0wt.%; Ni: 29.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0046] (1) Pure metal raw materials Fe (45.04 wt.%), Cr (21.0 wt.%), Ni (29.0 wt.%), Nb (0.6 wt.%), Mo (1.5 wt.%), and C (0.08 wt.%) were mixed in a crucible using a vacuum induction furnace and then smelted under vacuum (melting temperature was 1500°C and vacuum degree was 1 Pa). During smelting, a high vacuum environment and a low melting rate were used to enhance the efficiency of carbon deoxidation, nitrogen, phosphorus, and sulfur removal. After the steel was liquefied and cleared, the remaining amount of Al (2.5 wt.%) and Zr (0.1 wt.%) was added. After fully melting, the steel was refined at a refining temperature of 1500°C and a holding time of 10 minutes. At the same time, when the alloy liquid was maintained at 1500°C, 0.015 MPa of argon was injected to reduce the content of impurities O, N, P, and S in the material.
[0047] (2) The above solution was cast into an ingot at a pouring temperature of 1450°C, and then demolded to obtain a cast blank. The forging process was then carried out with the processing parameters of an initial forging temperature of 1200°C, a final forging temperature of 950°C, and a forging ratio of 5:1. The stainless steel forging blank round bar (20 mm diameter) was obtained by air cooling. After that, the forged material was heat treated with the specific parameters of solid solution treatment at 1000°C for 12 hours to ensure the uniformity of the material structure. The surface oxide film of the solid solution material was peeled off and pickled to obtain the master alloy round bar.
[0048] (3) The master alloy round rod is subjected to atomization powder spraying, with the atomization pressure controlled at 5 MPa, the superheat at 200°C, and the protective atmosphere being argon with a purity of not less than 99.999%, and the final master alloy powder having a particle size of 45-75 μm.
[0049] (4) Zr powder and Y2O3 powder were weighed and ball-milled, wherein the mass ratio of Zr powder to Y2O3 powder was 1.25 (based on the ratio of Zr: 0.1 wt.% and Y2O3: 0.08 wt.% in the total material content, and the total mass of the ball-milled Zr powder and Y2O3 powder was 180 g). Anhydrous ethanol was added as a process control agent during ball milling. Its mass fraction was 2.5% of the total mass of the powder. Argon gas with a purity of 99.9% was used during the ball milling process. The ball-to-material ratio was 8:1. The ball milling time was 50 h and the rotation speed was 200 r / min to obtain Zr-YO powder particles.
[0050] (5) The master alloy powder and Zr-YO powder particles were weighed in a mass ratio of 99.82:0.18, and then the two powders were fully mixed. The mixing method was as follows: the mixing atmosphere was argon protection of more than 99.999%; the mixing speed was 20 r / min; and the mixing time was 10 h.
[0051] (6) The uniformly mixed powders were then subjected to ball milling treatment, and the ball milling parameters were controlled as follows: the ball milling protective atmosphere was argon gas of 99.999% or more; the ball-to-material ratio was 8:1; the ball milling time was 100 h, and the rotation speed was 200 r / min.
[0052] (7) The mixed powder obtained in step (6) was pressed into shape by hot isostatic pressing (HIP) at a pressure of 150 MPa, a temperature of 1100°C, and a time of 5 h. The formed stainless steel was forged at an initial forging temperature of 1100°C, a final forging temperature of 950°C, and a total forging ratio of 5:1 to obtain a forged profile.
[0053] (8) The profiles were subjected to a two-step heat treatment of solution and aging, specifically as follows: the solution temperature was 1100°C, and the heat preservation time was 1 hour; the aging temperature was 600°C, and the heat preservation time was 200 hours.
[0054] Example 2
[0055] The raw material composition is as follows in terms of mass percentage: Cr: 21.5wt.%; Ni: 30.0wt.%; Al: 2.5wt.%; Mo: 2.0wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0056] (1) Pure metal raw materials Fe (43.04 wt.%), Cr (21.5 wt.%), Ni (30.0 wt.%), Nb (0.6 wt.%), Mo (2.0 wt.%), and C (0.08 wt.%) were mixed in a crucible using a vacuum induction furnace and then evacuated and smelted using electricity. During smelting, a high vacuum environment and a low melting rate were used to enhance the efficiency of carbon deoxidation, nitrogen, phosphorus, and sulfur removal. After the steel was liquefied and cleared, the remaining amount of Al (2.5 wt.%) and Zr (0.1 wt.%) was added. After fully melting, the steel was refined at a refining temperature of 1520°C and a holding time of 15 minutes. At the same time, when the alloy liquid was maintained at 1520°C, 0.015 MPa of argon was injected to reduce the content of impurities O, N, P, and S in the material.
[0057] (2) The above solution is poured into an ingot at a pouring temperature of 1450°C, and then demolded to obtain a casting blank; then forging is carried out with the processing parameters of an initial forging temperature of 1200°C, a final forging temperature of 950°C, and a forging ratio of 5:1; air cooling is performed to obtain a stainless steel forging billet round bar (20mm diameter). Afterwards, the forging material is heat treated with the following parameters: solution treatment at 1050°C for 12 hours to ensure the uniformity of the material structure; the surface oxide film of the material after solution treatment is peeled off and pickled to obtain a master alloy round bar;
[0058] (3) Afterwards, the master alloy round rod is subjected to atomization powder spraying, with the atomization pressure controlled at 5 MPa, the superheat at 200°C, and the protective atmosphere being argon with a purity of not less than 99.999%, and the particle size of the master alloy powder finally obtained being between 45-75 μm.
[0059] (4) Weighing Zr powder and Y2O3 powder for ball milling, wherein the mass ratio of Zr powder to Y2O3 powder is 1.25 (weighed according to the ratio of Zr: 0.1wt.%, Y2O3: 0.08wt.% in the total content of the material, and the total mass of the ball-milled Zr powder and Y2O3 powder is 180g); adding anhydrous ethanol as a process control agent during ball milling, the mass fraction of which is 2.5% of the total mass of the powder; using argon gas with a purity of 99.9% during ball milling; the ball-to-material ratio is 8:1; the ball milling time is 50h, and the rotation speed is 200r / min, to obtain Zr-YO powder particles;
[0060] (5) The master alloy powder and Zr-YO powder particles were weighed in a mass ratio of 99.72:0.28, and then the two powders were fully mixed. The mixing method was as follows: the mixing atmosphere was argon protection of more than 99.999%; the mixing speed was 20 r / min; and the mixing time was 10 h.
[0061] (6) The uniformly mixed powders were then ball-milled. During the ball milling, anhydrous ethanol was added as a process control agent with a mass fraction of 2.5% of the total mass of the powders. The ball milling parameters were controlled as follows: the ball milling protective atmosphere was argon gas with a mass fraction of more than 99.999%; the ball-to-material ratio was 8:1; the ball milling time was 100 h, and the rotation speed was 200 r / min.
[0062] (7) The mixed powder obtained in step (6) was pressed into shape by hot isostatic pressing (HIP) at a pressure of 150 MPa, a temperature of 1100°C, and a time of 5 h. The formed stainless steel was forged at an initial forging temperature of 1100°C, a final forging temperature of 950°C, and a total forging ratio of 5:1 to obtain a forged profile.
[0063] (8) The profiles were subjected to a two-step heat treatment of solution and aging, specifically as follows: the solution temperature was 1100°C, and the heat preservation time was 1 hour; the aging temperature was 600°C, and the heat preservation time was 200 hours.
[0064] Comparative Example 1
[0065] The difference from Example 1 is that, in terms of mass percentage, Cr: 25.0wt.%; Ni: 29.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0066] Comparative Example 2
[0067] The difference from Example 1 is that, in terms of mass percentage, Cr: 21.0wt.%; Ni: 25.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that, in terms of mass percentage, Cr: 21.0wt.%; Ni: 29.0wt.%; Al: 4.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0070] Comparative Example 4
[0071] The difference from Example 1 is that, in terms of mass percentage, Cr: 21.0wt.%; Ni: 29.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 1.2wt.%; Zr: 0.2wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0072] Comparative Example 5
[0073] The difference from Example 1 is that, in terms of mass percentage, Cr: 21.0wt.%; Ni: 29.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Y2O3: 0.08wt.%; C: 0.08wt.%; and the balance is Fe.
[0074] Comparative Example 6
[0075] The difference from Example 1 is that, in terms of mass percentage, Cr: 21.0wt.%; Ni: 29.0wt.%; Al: 2.5wt.%; Mo: 1.5wt.%; Nb: 0.6wt.%; Zr: 0.2wt.%; C: 0.08wt.%; and the balance is Fe.
[0076] Comparative Example 7
[0077] The difference from Example 1 is that the ball milling time of the mixed powder in step (6) is 25 h.
[0078] Comparative Example 8
[0079] The difference from Example 1 is that the final forging temperature in step (7) is 750°C.
[0080] Comparative Example 9
[0081] The difference from Example 1 is that in step (8), the solution temperature is 1250°C and the aging temperature is 700°C.
[0082] The stainless steel obtained in the examples and comparative examples was subjected to uniform corrosion tests in 550°C / 25MPa supercritical water and 550°C / 25MPa supercritical carbon dioxide, tensile tests in 550°C air, and Fe ion irradiation tests at 550°C. For the uniform corrosion test in supercritical water and the high-temperature tensile test, the test equipment used was a dynamic circulating supercritical water corrosion system designed independently by the research team; for the uniform corrosion test in supercritical carbon dioxide, the test equipment used was a dynamic circulating supercritical carbon dioxide corrosion system designed independently by the research team; the schematic diagram of the test equipment system is shown in the figure. Figure 5 、 6The Fe ion irradiation test was conducted using the 320kV high-charge ion integrated R&D platform of the Lanzhou Institute of Modern Physics. This platform is an open national experimental platform that can provide ions of more than 30 elements, including H, He, Bi, Fe, Si, Xe, Kr, Au, Ti, and U. The accelerating voltage is continuously adjustable within the ion energy range of 5keV-10MeV.
[0083] Two uniform corrosion tests were conducted using hanging specimens, with reference to the following standards: (1) ASTM E399 Standard Guide for Corrosion Tests in High Temperature or High Pressure Environment; (2) ASTM G111-97 (2013) Standard Guide for Corrosion Tests in High Temperature or High Pressure Environment; (3) GB / T 19291-2003 General Principles of Corrosion Testing of Metals and Alloys; and (4) JB / T 7901-2023 Laboratory Method for Uniform Corrosion of Metals by Full Immersion Test. Weighed, step-by-step polished specimens were hung in an autoclave using nickel-chromium alloy wire and subjected to 2000 hours of corrosion in a 550°C / 25 MPa supercritical water / supercritical carbon dioxide environment. The weight gain data was then obtained.
[0084] The high-temperature tensile test uses sheet tensile specimens, and the test standard refers to GB / T 228.2-2015 Tensile Tests on Metallic Materials (Part 2: High-Temperature Test Methods). The specimen is fixed to the tensile rod with a clamp, and then the installation mode is started to prevent any stress that may be introduced to the specimen during the autoclave closing process. The autoclave is then closed and the sealing bolts are tightened. After heating to the target temperature of 550°C, the air inlet and outlet valves are opened to keep the pressure in the autoclave consistent with the ambient pressure. Enter the specimen size parameters in the tensile test software and set the tensile rate to 10 -4 / s and click to start the test. Keep the stretching rate at 10 -4 / s until it breaks. The system will automatically record the data.
[0085] The ion irradiation test uses 5MeV Fe ions to irradiate the material at a temperature of 550 degrees Celsius. Through SRIM calculation and combined with the equipment flow control, the peak dose of the sample irradiation is 50dPa. Among them, the irradiated sample uses a 5×5×2mm 3 The surface of the sheet sample was polished to mirror smoothness. During the experiment, the temperature and vacuum degree of the irradiated sample were monitored to prevent surface oxidation caused by excessive temperature and oxidizing gas impurities.
[0086] The results are shown in Table 2.
[0087] Table 2
[0088]
[0089] As shown in Table 2, the test shows that, compared with Example 1, although the increase in the Cr content in Comparative Example 1 increases the corrosion resistance of the material in supercritical water and supercritical carbon dioxide environments, the excessively high Cr content causes a brittleness problem, resulting in a significant decrease in the radiation resistance and mechanical properties of the material; Comparative Example 2 reduces the Ni content, resulting in the precipitation and growth of the Sigma phase in the material. At the same time, the Laves phase also coarsens, and the strengthening phase Ni3Al is reduced, resulting in a decrease in the mechanical properties and radiation resistance of the material; Comparative Example 3 has an excessively high Al content, which enhances the formation of the oxide film. Although this greatly improves the corrosion resistance of the material, it leads to uneven distribution of the oxide, and the high Al content causes it to react with Y2O3 to form coarse oxides, which weakens the radiation resistance and mechanical properties; Comparative Example 4 has a higher Nb content, resulting in an uneven distribution of the strengthening phase, which reduces The mechanical properties of the material are improved; in Comparative Example 5, no Zr is added, resulting in poor dispersion strengthening effect, the appearance of coarse Al-YO phase, and the lack of Zr reduces the material's ability to capture radiation defects; in Comparative Example 6, no Y2O3 is added, resulting in the inability of the material to form a dispersion strengthening phase Zr-YO, which reduces the corrosion resistance to supercritical water and supercritical carbon dioxide, and seriously reduces the radiation resistance; in Comparative Example 7, insufficient ball milling time leads to insufficient and uneven distribution of the dispersion strengthening phase, which reduces the radiation resistance of the material; in Comparative Example 8, cracking occurs during the forging process, resulting in failure of material preparation, and the final forging temperature is too low, resulting in the inability of the material to maintain plastic deformation and eventually cracking; in Comparative Example 9, the solution temperature and aging temperature are too high, resulting in coarse grains and precipitated phases, which leads to a decrease in the corrosion resistance of the material, and the high-temperature elongation of the material is significantly reduced compared with the embodiment.
[0090] Figure 1 The morphology of the dispersed oxides in the oxide dispersion-strengthened new austenitic stainless steel material obtained in Example 1 of the present invention is shown. It can be seen that the particles are uniform in size and dispersed in the matrix, with an average particle size of less than 20 nm, which helps to suppress radiation swelling and strengthen the matrix properties. Figure 2 、 Figure 3 The following are the morphologies of the oxide film of Example 1 of the present invention after corrosion for 1000 hours in supercritical water and supercritical carbon dioxide at 550°C. The oxide film thickness in the supercritical water environment is about 600 nm, while the oxide film thickness in the supercritical carbon dioxide environment is about 400 nm. In both cases, a continuous Al2O3 oxide film is formed, indicating that the present invention has good corrosion resistance in both corrosion environments, and a uniformly dispersed strengthening phase can be observed. Figure 4This image shows irradiation voids in Example 1 after irradiation with 5MeV iron ions at 550°C. The number of irradiation voids formed in the material of Example 1 after 5MeV iron ion irradiation is extremely small, and the void diameter is less than 5nm. This demonstrates the effectiveness of the dispersion-strengthened phase, which can capture point defects generated by irradiation and inhibit void growth.
[0091] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, and all of these should be included in the scope of the present invention.
Claims
1. An oxide dispersion strengthened austenitic stainless steel, characterized by: Contains elements Cr, Ni, Al, Mo, Nb, Zr, Y2O3, C and Fe; Calculated based on the mass fraction of the raw materials, the mass fraction of Cr is 20.0-22.0wt.%, the mass fraction of Ni is 28.0-30.0wt.%, the mass fraction of Al is 2.0-3.0wt.%, the mass fraction of Mo is 1.0-2.0wt.%, the mass fraction of Nb is 0.6-1.0wt.%, the mass fraction of Zr is 0.1-0.4wt.%, the mass fraction of Y2O3 is 0.05-0.15wt.%, the mass fraction of C is 0.06-0.1wt.%, and the balance is Fe.
2. The oxide dispersion strengthened austenitic stainless steel according to claim 1, wherein: Calculated by mass fraction, the mass fraction of Cr is 21.0wt.%; the mass fraction of Ni is 29.0wt.%; the mass fraction of Al is 2.5wt.%; the mass fraction of Mo is 1.5wt.%; the mass fraction of Nb is 0.6wt.%; the mass fraction of Zr is 0.2wt.%; the mass fraction of Y2O3 is 0.08wt.%; the mass fraction of C is 0.08wt.%; and the balance is Fe.
3. The oxide dispersion strengthened austenitic stainless steel according to claim 1 or 2, characterized in that: It also has the following features: (i) Corrosion in 550℃ / 25MPa supercritical water for 2000h increases weight by 14.26-14.72mg·dm 2 ; (ii) Corrosion in supercritical carbon dioxide at 550°C / 25 MPa for 2000 h increases weight by 5.45 to 5.53 mg·dm 2 ; (iii) the swelling ratio after 50 dpa of Fe ion irradiation at 550 °C was 0.31–0.34%; (iiii) The tensile elongation at 550°C is 35.2-36.4%.
4. A method for preparing oxide dispersion-strengthened austenitic stainless steel, characterized in that: include, Fe, Cr, Ni, Nb, Mo and C are mixed and then vacuumed and sent for electric melting. After the steel is liquefied and cleared, Al and Zr are added and refined under vacuum conditions, followed by pouring, forging, heat treatment and gas atomization powder spraying to obtain master alloy powder. Zr powder and Y2O3 powder were ball-milled in a high-purity argon atmosphere to obtain Zr-YO powder; The master alloy powder and the Zr-YO powder are ball-milled in a high-purity argon atmosphere to obtain a mixed powder; The mixed powder is hot isostatically pressed and solidified, and then forged and heat treated to obtain the compound dispersion strengthened austenitic stainless steel.
5. The preparation method according to claim 4, wherein: The refining temperature is 1470-1530° C., and the refining time is 8-12 minutes.
6. The preparation method according to claim 4, wherein: The Zr powder and Y2O3 powder are ball-milled in a high-purity argon atmosphere to obtain Zr-YO powder, wherein the mass ratio of Zr to Y elements is not less than 1.03; the mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-material ratio is 5-10:1, the ball milling time is 25-50 hours, and the rotation speed is 200-400 r / min.
7. The preparation method according to claim 4, wherein: The master alloy powder and Zr-YO powder are ball-milled and mixed in a high-purity argon atmosphere to obtain a mixed powder, and the mass of the Zr-YO powder is controlled so that the total content of Y2O3 does not exceed 0.15%. The mass fraction of anhydrous ethanol added during ball milling is 2.5% of the total mass of the powder; the ball-to-material ratio is 6-12:1; the ball milling time is 50-150 hours, and the rotation speed is 150-300 r / min.
8. The preparation method according to claim 4, wherein: The mixed powder is hot isostatically pressed and solidified, and then forged and heat treated to obtain the compound dispersion strengthened austenitic stainless steel, wherein the forging conditions are an initial forging temperature of 1100-1200°C, a final forging temperature of not less than 950°C, and a total forging ratio of not less than 4:
1.
9. The preparation method according to claim 8, wherein: The heat treatment includes solid solution and aging, wherein the solid solution temperature is 1100-1200° C. and the holding time is 1-2 hours; the aging temperature is 550-650° C. and the holding time is 100-200 hours.
10. Use of the oxide dispersion strengthened austenitic stainless steel according to claims 1 to 3 in supercritical water / supercritical carbon dioxide cooled nuclear reactor cladding materials.